Differential item functioning in the Patient Reported Outcomes Measurement Information System Pediatric Short Forms in a sample of children and adolescents with cerebral palsy - Coster, Wendy J (Dev Med Child Neurol, 2016)
AIM: The present study examined the Patient Reported Outcomes Measurement Information System (PROMIS) Mobility, Fatigue, and Pain Interference Short Forms (SFs) in children and adolescents with cerebral palsy (CP) for the presence of differential item functioning (DIF) relative to the original calibration sample. METHOD: Using the Graded Response Model we compared item parameter estimates generated from a sample of 303 children and adolescents with CP (175 males, 128 females; mean age 15y 5mo) to parameter estimates from the PROMIS calibration sample, which served as the reference group. DIF was assessed in a two-step process using the item response theory–likelihood ratio–differential item functioning detection procedure. RESULTS: Significant DIF was identified for four of eight items in the PROMIS Mobility SF, for two of eight items in the Pain Interference Scale, and for one item out of 10 on the Fatigue Scale. Impact of DIF on total score estimation was notable for Mobility and Pain Interference, but not for Fatigue. INTERPRETATION: Results suggest differences in the responses of adolescents with CP to some items on the PROMIS Mobility and Pain Interference SFs. Cognitive interviews about the PROMIS items with adolescents with varying degrees of mobility limitations would provide better understanding of how they are interpreting and selecting responses to the PROMIS items and thus help guide selection of the most appropriate way to address this issue.